Dual Effect of Acetic Acid Efficiently Enhances Sludge-Based Biochar to Recover Uranium From Aqueous Solution - Yu, Shoufu; Wu, Xiaoyan; Ye, Jian; Li, Mi; Zhang, Qiucai; Zhang, Xiaowen; Lv, Chunxue; Xie, Wenjie; Shi, Keyou; Liu, Yong (Frontiers in Chemistry, 2022)
Excess sludge (ES) treatment and that related to the uranium recovery from uranium-containing wastewater (UCW) are two hot topics in the field of environmental engineering. Sludge-based biochar (SBB) prepared from ES was used to recover uranium from UCW. Excellent effects were achieved when SBB was modified by acetic acid. Compared with SBB, acetic acid-modified SBB (ASBB) has shown three characteristics deserving interest: 1) high sorption efficiency, in which the sorption ratio of U(VI) was increased by as high as 35.0%; 2) fast sorption rate, as the equilibrium could be achieved within 5.0 min; 3) satisfied sorption/desorption behavior; as a matter of fact, the sorption rate of U(VI) could still be maintained at 93.0% during the test cycles. In addition, based on the test conditions and various characterization results, it emerged as a dual effect of acetic acid on the surface of SBB, i.e., to increase the porosity and add (−COOH) groups. It was revealed that U(VI) and −COO− combined in the surface aperture of ASBB via single-dentate coordination. Altogether, a new utilization mode for SBB is here proposed, as a means of efficient uranium sorption from UCW.